Characterization of a Novel Pectate Lyase from Erwinia carotovora subsp. carotovora - Heikinheimo, Riikka (Molecular plant-microbe interactions, 1995)
The pectate lyase (Pel, EC 4.2.2.2) isoenzyme profile of Erwinia carotovora subsp. carotovora was characterized by isoelectric focusing, and the corresponding genes coding for four different exported Pels were cloned. The nucleotide sequence of the pelB gene encoding one of these isoenzymes was determined and was shown to contain 1,040-bp open reading frame coding for a 37,482-Da protein with a putative cleavable amino terminal signal peptide. Overexpression and selective labeling experiments with the pelB clone demonstrated the synthesis of a 35-kDa polypeptide, which is in accordance with the deduced size of the processed PelB. The predicted amino acid sequence of PelB was very similar to that of Pel-3 of another E.c. subsp. carotovora strain 71, but showed no similarity to other previously characterized pectinolytic enzymes. The pelB gene is located next to the previously characterized pehA gene encoding an endopolygalacturonase. The two genes are divergently transcribed from a common control region and are subject to similar global regulation by the central virulence regulator expI. Inactivation of pelB did not appear to reduce the virulence of the mutant strain, suggesting that pelB does not have a major role in pathogenicity. Unlike other Pels, PelB required partially methyl esterified pectin as substrate suggesting that PelB represents a novel isoform of pectate lyase.